2016
DOI: 10.1515/ama-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Fatigue of Steel in Strain Controled Cyclic Bending

Abstract: The paper presents a comparison of the fatigue life curves based on test of 15Mo3 steel under cyclic, pendulum bending and tension-compression. These studies were analyzed in terms of a large and small number of cycles where strain amplitude is dependent on the fatigue life. It has been shown that commonly used Manson-Coffin-Basquin model cannot be used for tests under cyclic bending due to the impossibility of separating elastic and plastic strains. For this purpose, some well-known models of Langer and Kandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A part of the research data was obtained from the available literature, and some data were obtained from our own research. The analyzed and tested materials were 10HNAP, based on our research under tension-compression [27] and under bending [28]; 16Mo3, based on data from the literature for tension-compression [29] and on the basis of our own tests for bending [30]; 30CrNiMo3, based on data from the literature for bending [30] and tension-compression [31]; MO58, on the basis of our own tests for bending [32] and for tension-compression [33]; SM45, based on data from the literature for bending [34] and for tension-compression [29]; 2017A-T4, based on our own tests under bending [35] and tension-compression [36]; and 6082-T6, also on the basis of our own tests under bending [37] and tension-compression [38]. Table 1 presents the chemical composition of tested materials, and Table 2 presents the mechanical properties of these materials.…”
Section: Experimental Testsmentioning
confidence: 99%
“…A part of the research data was obtained from the available literature, and some data were obtained from our own research. The analyzed and tested materials were 10HNAP, based on our research under tension-compression [27] and under bending [28]; 16Mo3, based on data from the literature for tension-compression [29] and on the basis of our own tests for bending [30]; 30CrNiMo3, based on data from the literature for bending [30] and tension-compression [31]; MO58, on the basis of our own tests for bending [32] and for tension-compression [33]; SM45, based on data from the literature for bending [34] and for tension-compression [29]; 2017A-T4, based on our own tests under bending [35] and tension-compression [36]; and 6082-T6, also on the basis of our own tests under bending [37] and tension-compression [38]. Table 1 presents the chemical composition of tested materials, and Table 2 presents the mechanical properties of these materials.…”
Section: Experimental Testsmentioning
confidence: 99%
“…where: K' -cyclic strengthening coefficient, n' -cyclic strengthening exponent. This characteristic is needed for determining elastic-plastic strains in the event of bending at the controlled moment and for dividing the strain amplitude into an elastic part and plastic part at bending and strain controlling [14].In case we have data from uniaxial tension-compression, Ramberg-Osgood equation constants (2), i.e. K' and n', we can separate an elastic and plastic part of the strain amplitude.…”
Section: Fatigue Testing Of Steel and Aluminiummentioning
confidence: 99%
“…A few studies on bending fatigue testing in the LCF regime have been conducted to evaluate the size effect and the influence of strain gradient on fatigue failure life. Kulesa et al [9], Kurek et al [10], and Kurek [11] developed a lab-made bending testing apparatus to conduct strain-controlled cyclic bending and evaluated the relationship between fatigue failure life and total strain amplitude. They demonstrated that the fatigue life of bending specimens was slightly longer than that of T/C specimens.…”
Section: Introductionmentioning
confidence: 99%